Clinical Evaluation of an NVTIA β-Carotene–Grape Seed Extract Retinal Protection Formulation - Yassine, Jabar; Turner, Malik; Semenza, Gregg L. (Scientific Journal of Technology, 2026)
We evaluated an eight-component retinal-support formulation that combines lutein, meso-zeaxanthin, β-carotene, blueberry extract, grape seed extract, L-ergothioneine, saffron extract, and phosphatidylserine within a dual-phase microencapsulation platform. We retained the available formulation-characterization dataset for lipid-soluble oxidation, water-soluble retention, 45-minute dissolution, and blue-light–stressed retinal pigment epithelial survival, and we paired those data with published randomized or controlled human trials across the clinically closest ingredient domains. Embodiment 1 limited oxidation of lipid-soluble components to 0.8%, preserved 99.2% of water-soluble actives, reached 92.5% dissolution at 45 minutes, and maintained 89.7% retinal pigment epithelial cell survival after blue-light induction. Published human evidence was strongest for the carotenoid and saffron pillars: AREDS2 enrolled 4203 participants and supported lutein/zeaxanthin as a safer and clinically preferable substitute for β-carotene in at-risk age-related macular degeneration populations; meso-zeaxanthin-containing carotenoid trials improved macular pigment and glare-related contrast sensitivity; and saffron supplementation improved retinal electrophysiology and modestly improved best-corrected visual acuity in mild-to-moderate age-related macular degeneration. Anthocyanin-rich berry extract reduced video-display-terminal–related ocular fatigue, and grape seed proanthocyanidin extract improved hard exudates in non-proliferative diabetic retinopathy. In our search, direct randomized retinal-endpoint trials centered on ergothioneine or phosphatidylserine were not identified. We conclude that the formulation has a credible translational rationale for retinal protection, with human evidence distributed unevenly across its component domains rather than concentrated in a completed trial of the exact finished formula.